Navigated percutaneous cervical pedicle screw placement: the impact of surgical experience and feasibility - Gierse, Jula; Klockow, Kevin; Mandelka, Eric; Bullert, Benno; Brunken, Fenna; Grützner, Paul Alfred; Vetter, Sven Y. (World neurosurgery, 2025)
Objective - Surgical treatment of cervical instabilities using pedicle screws poses risks of nerve and vessel injury, particularly in percutaneous procedures due to limited visual feedback. Navigation can reduce screw misplacement, but data on its usability across different experience levels in percutaneous approaches remains limited. - Methods - Two surgeons performed navigated cervical pedicle screw placement on human specimens using two C-arm cone-beam computed tomography-based navigation systems (navigation system 1 [NAV1], navigation system 2). One surgeon was an experienced spine surgeon, and the other was a second-year resident (RS). Screw position was assessed via C-arm cone-beam computed tomography scans, and placement time was recorded. - Results - A total of 112 screws were placed, 56 per surgeon/system. Accuracy comparisons showed no significant difference (P = 0.060). However, RS achieved significantly better accuracy with NAV1 (P = 0.037∗). Experienced spine surgeon achieved an accuracy rate of 89.3% with NAV1 and 85.7% with navigation system 2 (P > 0.99), requiring significantly less time than RS (P < 0.001∗∗). - Conclusions - This study provides valuable insights into the feasibility and challenges of navigated percutaneous cervical pedicle screw placement. Both surgeons achieved accurate screw placement; however, the differences in RS's accuracy highlight the pivotal role of experience in cervical spine surgery for the safe application of navigation systems. Additionally, this study identifies pitfalls that should be considered in clinical practice and in the education of young spine surgeons when adopting new technologies.